ENPP4 and HOXA3 as potential leukaemia stem cell markers in acute myeloid leukaemia - Mohd Amin, A; Panneerselvan, N; Md Noor, S; Mohtaruddin, N; Sathar, J; Norbaya, WS; Osman, R; Kee, LH; Mohd Yaaku, WH; Cheong, SK; Abdullah, M (Malaysian Society of Pathologists, 2023)
Introduction: Acute myeloid leukaemia (AML) is a heterogeneous malignant disease with a high degree of treatment failure using chemotherapy. Leukaemia stem cells (LSCs) are CD34+CD38- early progenitors associated with poor prognosis in AML. A unique LSC phenotype that excludes rare normal haematopoietic stem cells (HSC) is still elusive. This study aimed to determine expression of selected potential LSC markers in normal and leukaemic myeloid cells and correlate prognosis in AML patients.